The Extraterritorial Application of Human Rights Treaties in the Context of Environmental Transboundary Harm - Kazım Berkay Arslan (Public and Private International Law Bulletin, 2022)
This article treats the issue of jurisdiction under human rights treaties in cases of environmental transboundary harm. It aims to cover the definitions of the environment and transboundary harm as well as the relevant rules under international environmental law applicable to environmental transboundary harm. Thereafter, it analyses the territorial scope of human rights treaties and focuses on the establishment of a jurisdictional link in cases of environmental transboundary damages. It suggests that the classical approach, which is focused on effective control over an area or persons, is not apt in this context. Rather, this article proposes the use of other approaches to jurisdiction, such as the functional approach adopted by the Inter-American Court of Human Rights which is based on an effective control over the activities causing environmental harm and consequent human rights violations. It further argues that the general rule under customary international law which prohibits States from engaging in acts causing transboundary harm could also be applied as a special feature in the context of international human rights law. Finally, this article concludes by pointing out some current challenges that need to be clarified with respect to the obligations of States arising from human rights breaches caused by environmental transboundary damages.